2015
DOI: 10.1097/ico.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Corneal Graft Rejection

Abstract: Prednisolone remains the treatment of choice for management and treatment of graft rejection; however, since the introduction of difluprednate, its use has declined slightly since the introduction of difluprednate. Despite perceived differences in rejection rates, there were no differences in prophylactic steroid treatment for PK and EK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…Surprisingly, the usage of subconjunctival steroid preparations was noted to be higher in routine management of low-risk grafts (76%) than in high-risk grafts (54%); this may be related to the use of other topical and oral immunosuppressive agents in high-risk grafts. 82 …”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the usage of subconjunctival steroid preparations was noted to be higher in routine management of low-risk grafts (76%) than in high-risk grafts (54%); this may be related to the use of other topical and oral immunosuppressive agents in high-risk grafts. 82 …”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…82,123,124 However, no randomized clinical trial has been performed to assess the efficacy of this therapy. The Bowman Club Survey in the United Kingdom demonstrated that 44% of corneal surgeons use systemic immunosuppression including oral prednisolone for 1 day to 12 months postoperatively in high-risk cases.…”
Section: Management Of High-risk Corneal Transplantationmentioning
confidence: 99%
“…Surveys indicate that prednisolone acetate 1% is the preferred topical steroid for the prevention of transplant rejection. [7][8][9] Loteprednol etabonate differs from other corticosteroids because it has an ester instead of a ketone at the C-20 position of the core corticosteroid structure. 6 After ocular penetration, unbound loteprednol etabonate undergoes rapid deesterification to an inactive metabolite, which is believed to reduce the potential impact on intraocular pressure (IOP).…”
mentioning
confidence: 99%
“…[20] In the past, this treatment has proven effective in improving survival rates of LR corneal transplantation patients. [21] However, the duration of prophylactic treatment with topical corticosteroids is still variable among surgeons.…”
Section: High-risk Corneal Transplantationmentioning
confidence: 99%
“…[21] However, the duration of prophylactic treatment with topical corticosteroids is still variable among surgeons. [20]…”
Section: High-risk Corneal Transplantationmentioning
confidence: 99%